Knowledge and practices pertaining to menstruation among the school going adolescent girls of UHTC/RHTC area of Government Medical College, Kota, Rajasthan - Gupta, Preeti; Gupta, Jini; Singhal, Govind; Meharda, Bharat (International Journal Of Community Medicine And Public Health, 2018)
Background: To achieve the goal of Millennium Development Goal 2 (universal education), 3 (gender equality and women empowerment) and, 5 (improving maternal health), it is important that there is effective menstrual hygiene and knowledge among adolescent girls since it has direct and indirect effects both to achieve the MDG and to promote the reproductive health. A study was carried out among the school going adolescents in UHTC (Urban Health Training centre) and RHTC (Rural Health Training centre) area of Department of Community Medicine, Government Medical College, Kota, Rajasthan with the following aims and objectives, Status of knowledge of school going adolescent girls about menstruation and their practice during menstruation. The objective of the study was to assess the knowledge and practices regarding menstruation among school going adolescents. Methods: It was a school based descriptive cross sectional study conducted from November 2016 to March 2017. The school was selected randomly in RHTC and UHTC area of GMC, Kota. A pretested and structured questionnaire was used. Data was entered, processed and analyzed using SPSS version 20. Results: In this study there were 300 girl students (150 each from RHTC and UHTC area schools), of which 55.33% had menarche at the age of 13 years, 66.00% of girls were aware about menstruation before the menarche whereas 91.67% of girls heard about the sanitary napkins, most of the girls (81.00%) had got the knowledge about menses from their mother, 62.67% of girls heard about the menstrual hygiene and for practices observed, 65.67% girls were using sterilized sanitary napkins and 42.00% of girls burn the waste material. Conclusions: Traditional beliefs regarding menstruation still persist and menstrual hygiene among the adolescents was found to be unsatisfactory. It highlights the need of targeted interventions to raise awareness and provision of family health education package to all girls. Menstrual hygiene is an issue that needs to be addressed at all levels.